2021
DOI: 10.1007/s00167-021-06558-z
|View full text |Cite
|
Sign up to set email alerts
|

Return to preinjury sports after anterior cruciate ligament reconstruction is predicted by five independent factors

Abstract: Purpose To determine factors that predict return to the same frequency and type of sports participation with similar activity demands as before injury. Methods Individuals 1 to 5 years after primary ACL reconstruction completed a comprehensive survey related to sports participation and activity before injury and after surgery. Patient characteristics, injury variables, and surgical variables were extracted from the medical record. Return to preinjury sports (RTPS) was deined as: "Returning to the same or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
(57 reference statements)
0
18
1
Order By: Relevance
“…6,44 The differences might be because of the diversity of demographic characteristics among studies, given that younger athletic patients with acute ACL injuries are more likely to return to preinjury sports. 31 Compared with the findings of Chen et al, 6 the present study revealed a higher rate of return to pivoting sports and a lower rate of residual pivot shift or clinical failure in the ACLR group. This might be attributed to the different inclusion criteria, wherein our study population had more acute ACL injuries and less morphological abnormity or high-grade preoperative knee laxity.…”
Section: Discussioncontrasting
confidence: 67%
“…6,44 The differences might be because of the diversity of demographic characteristics among studies, given that younger athletic patients with acute ACL injuries are more likely to return to preinjury sports. 31 Compared with the findings of Chen et al, 6 the present study revealed a higher rate of return to pivoting sports and a lower rate of residual pivot shift or clinical failure in the ACLR group. This might be attributed to the different inclusion criteria, wherein our study population had more acute ACL injuries and less morphological abnormity or high-grade preoperative knee laxity.…”
Section: Discussioncontrasting
confidence: 67%
“…In contrast, long chronicity of ACL tear has been reported to result in a lower rate of return to sports and a higher rate of long-term osteoarthritis after ACLR. 4,24 Therefore, ascertaining the principal requirement among these outcomes and managing the expectations for surgical treatment are crucial. For instance, the top priority for young, competitive athletes who have acute ACL tears is to return to preinjury levels of sport rather than to achieve MCIDs, and early surgical treatment with personalized rehabilitation schemes adjusted for the risk of clinical failure may be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…4,15,20,32,33 Sports levels, baseline patient-reported outcome measures (PROMs), preoperative knee laxity, surgical procedures, and postoperative rehabilitation have been revealed to highly correlate with these clinical outcomes of ACLR. 1,6,11,21,24 However, the discrepant absolute or relative risks of every single predictor resulting from regression analyses in different studies are confusing in clinical practice. Clinicians may find it difficult to predict a specific outcome with an exact likelihood and improve the treatment scheme based on just 1 or 2 risk factors in a patient.…”
mentioning
confidence: 99%
“… 3 , 10 , 29 Noted discrepancies across studies are often based on age, sex, specific sport, level of participation, and differences in surgical technique and postoperative rehabilitation. 6 , 21 , 24 , 28 30 Ardern et al 3 examined a cohort of 314 competitive athletes, demonstrating 93% RTS at both the competitive and the recreational levels. Lai et al 24 found that, in general, 83% of elite athletes (professional, National Collegiate Athletic Association Division I, or highest level of competition for their sport) were able to RTS after ACLR within 12 months.…”
Section: Discussionmentioning
confidence: 99%